Surface Treatment With Hydrophobic Coating Reagents (Organosilanes) Strongly Reduces the Bioactivity of Synthetic Amorphous Silica in vitro - Wiemann, Martin; Vennemann, Antje; Schuster, Tobias B.; Nolde, Jürgen; Krueger, Nils (Frontiers in Public Health, 2022)
Synthetic amorphous silica (SAS) is industrially relevant material whose bioactivity in vitro is strongly diminished, for example, by protein binding to the particle surface. Here, we investigated the in vitro bioactivity of fourteen SAS (pyrogenic, precipitated, or colloidal), nine of which were surface-treated with organosilanes, using alveolar macrophages as a highly sensitive test system. Dispersion of the hydrophobic SAS required pre-wetting with ethanol and extensive ultrasonic treatment in the presence of 0.05% BSA (Protocol 1). Hydrophilic SAS was suspended by moderate ultrasonic treatment (Protocol 2) and also by Protocol 1. The suspensions were administered to NR8383 alveolar macrophages under serum-free conditions for 16 h, and the release of LDH, GLU, H2O2, and TNFα was measured in cell culture supernatants. While seven surface-treated hydrophobic SAS exhibited virtually no bioactivity, two materials (AEROSIL® R 504 and AEROSIL® R 816) had minimal effects on NR8383 cells. In contrast, non-treated SAS elicited considerable increases in LDH, GLU, and TNFα, while the release of H2O2 was low except for CAB-O-SIL® S17D Fumed Silica. Dispersing hydrophilic SAS with Protocol 1 gradually reduced the bioactivity but did not abolish it. The results show that hydrophobic coating reagents, which bind covalently to the SAS surface, abrogate the bioactivity of SAS even under serum-free in vitro conditions. The results may have implications for the hazard assessment of hydrophobic surface-treated SAS in the lung.